2010
DOI: 10.1016/j.neuroimage.2010.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Removal of BCG artifacts from EEG recordings inside the MR scanner: A comparison of methodological and validation-related aspects

Abstract: Multimodal approaches are of growing interest in the study of neural processes. To this end much attention has been paid to the integration of electroencephalographic (EEG) and functional magnetic resonance imaging (fMRI) data because of their complementary properties. However, the simultaneous acquisition of both types of data causes serious artifacts in the EEG, with amplitudes that may be much larger than those of EEG signals themselves. The most challenging of these artifacts is the ballistocardiogram (BCG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
106
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(108 citation statements)
references
References 52 publications
2
106
0
Order By: Relevance
“…The standardized strategy to correct PA relies on Average Artifact Subtraction, AAS (Allen et al 1998), which can be complemented by estimating an Optimal Basis Set of principal components (Niazy et al 2005) and/or by an ICA (Independent Component Analysis) decomposition to remove residual artifacts (Debener et al 2007;Vanderperren et al 2010). Other authors proposed a direct ICA on EEG (Benar et al 2003;Marques et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The standardized strategy to correct PA relies on Average Artifact Subtraction, AAS (Allen et al 1998), which can be complemented by estimating an Optimal Basis Set of principal components (Niazy et al 2005) and/or by an ICA (Independent Component Analysis) decomposition to remove residual artifacts (Debener et al 2007;Vanderperren et al 2010). Other authors proposed a direct ICA on EEG (Benar et al 2003;Marques et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Manual selection was performed by Mantini et al (2007) and Huiskamp (2006). Vanderperren et al (2010) employed more complex criteria set for component selection, which was based on several parameters: correlation, frequency content, autocorrelation, variance and peak-to-peak amplitude of reconstructed sources. However, daEEG allows utilization of a simple principle for independent component selection: components whose spatial distribution is independent of EEG cable arrangements correspond with brain activity, while those that are influenced by EEG cable arrangements correspond with motion artifacts (either BCG or non-BCG).…”
Section: Discussionmentioning
confidence: 99%
“…For example, LeVan et al (2013) found distortions of the EEG data following OBS in the form of attenuation of alpha oscillations and Liu et al (2012) found that OBS induced spurious lowfrequency (3-8 Hz) components that were absent in the clean EEG spectrum. These distortions may be due to the suboptimal choice of the number of components used (LeVan et al, 2013) or suboptimal detection of QRS events (Vanderperren et al, 2010). Alternatively, this increase in peak-to-peak amplitude can also be a result of the hybrid procedure itself.…”
Section: Discussionmentioning
confidence: 99%
“…Another study investigated the effects of two common pulse artefact correction methods on the quality of auditory event-related potentials (ERP's) (Debener et al 2007). A more recent study attempted to validate pulse artefact correction methods by using detailed criteria based on the average ERP's as well as their trial-by-trial modulations (Vanderperren et al 2010). For the evaluation of the reduction of the gradient artefact, a method based on both the amount of artefact reduction and that of biosignal preservation, in different frequency bands, has been proposed (Freyer et al 2009).…”
Section: Discussionmentioning
confidence: 99%